Train Traffic Simulation with Coloured Petri Nets and Schedule Optimisation - Bartkevičius, S.; Bagdonas, V.; Juraška, M.; Šarkauskas, K. (Elektronika ir Elektrotechnika, 2005)
The article provides the methodology of train traffic schedule optimisation according to minimum overall expenditure criteria. Simulation of traffic processes is used in the algorithm of optimisation. For this reason a software tool theoretically based on coloured Petri nets has been created. The major advantage of the model is the convenience of observation of the situation simulation as its configuration corresponds to the real configuration of the tracks. Ill. 7, bibl. 10 (in English, summaries in Lithuanian, English, Russian).